Managing venous thrombosis in a pediatric patient with short bowel and congenital nephrotic syndromes: a case report emphasizing rivaroxaban level monitoring - Bosch-Schips, Marc; Artaza, Gonzalo; Hernández-Mata, Carlos; Pérez Beltrán, Víctor; Cabello Ruiz, Vanessa; Olivera Sumire, Pável (Frontiers in Pediatrics, 2024)
Direct Oral Anticoagulants (DOACs) typically exhibit a predictable pharmacokinetic and pharmacodynamic response at a fixed dose, not necessitating monitoring under standard conditions. Yet, in specific clinical scenarios that can impair it, like Congenital Nephrotic Syndrome (CNS) or Short Bowel Syndrome (SBS) due to absorption issues, anti-thrombin III (AT-III) deficiency and non-selective proteinuria, adjusting the dosage to achieve appropriate plasma concentrations could prove beneficial. We report a 3-month-old female with catheter-related jugular thrombosis affected by CNS concomitant to SBS and failure of both treatments with heparin and warfarin, that was switched to dose-adjusted pediatric rivaroxaban. Rivaroxaban was adjusted to reach peak levels between 189 and 419 ng/mL and the lower trough levels between 6 and 87 ng/mL. Increasing doses were needed due to SBS related malabsorption but a complete permeabilization of the vein was achieved without bleeding complications. The use of anti-Xa adjusted rivaroxaban could be an alternative to improve anticoagulation and secondary thromboprophylaxis in pediatric patients SBS and an option to children with CNS.